Serum Proteomic Analysis by Tandem Mass Tag-Based Quantitative Proteomics in Pediatric Obstructive Sleep Apnea - Cheng, Hanrong; Jin, Shoumei; Huang, Simin; Hu, Tianyong; Zhao, Miao; Li, Dongcai; Wu, Benqing (Frontiers in Molecular Biosciences, 2022)
Pediatric obstructive sleep apnea (OSA) is a frequent respiratory disorder with an estimated prevalence of 3–6% in the general population. However, the underlying pathophysiology of OSA remains unclear. Recently, proteomic analysis using high-resolution and high-throughput mass spectrometry has been widely used in the field of medical sciences. In the present study, tandem mass tags (TMT)-based proteomic analysis was performed in the serum of patients with OSA. The proteomic analysis revealed a set of differentially expressed proteins that may be associated with the pathophysiology of OSA. The differentially expressed proteins in patients with OSA were enriched in pathways including phagosome, glycan synthesis/degradation, immune response, hedgehog signaling pathway, indicating that such functions are key targets of OSA. Moreover, the experimental validation studies revealed that four proteins including ANTXR1, COLEC10, NCAM1 and VNN1 were reduced in the serum from patients moderate and severe OSA; while MAN1A1 and CSPG4 protein levels were elevated in the serum from patients with severe OSA. The protein levels of ANTXR1, COLEC10, NCAM1 and VNN1 were inversely correlated with AHI in the recruited subjects; while the protein level of MAN1A1 was positively correlated with AHI, and no significant correlation was detected between CSPG4 protein and AHI. In summary, the present study for the first time identified differentially expressed proteins in the serum from OSA patients with different severity by using TMT-based proteomic analysis. The functional enrichment studies suggested that several signaling pathways may be associated with the pathophysiology of OSA. The experimental validation results indicated that six proteins including ANTXR1, COLEC10, NCAM1, VNN1, CGPG4 and MAN1A1 may play important roles in the pathophysiology of OSA, which requires further mechanistic investigation.